Distribution, sources and toxicity of polycyclic aromatic hydrocarbons in Liuxi River, China. Issue 4 (21st April 2022) - Min, Wang; Lei, Tian; Jingxin, Sun; Zhang, Yutong; Hongqin, Zhai; Dong, Li; Lin, Wan
ABSTRACT: The distribution characteristics and resources (in plentiful and dry seasons) of polycyclic aromatic hydrocarbons (PAHs) in the Liuxi River were analyzed and toxicity of typical PAHs to biological cells were assessed. The results showed that: Compared with the dry season, the species and content of PHAs in Liuxi River are fewer in the plentiful season. In the plentiful season, 7 kinds of PHAs were detected, and the total PAHs content (∑PAHs) in each sampling point ranges from 73.2 to 258.5 ng/g. While in the dry season, 13 kinds of PHAs were detected, and the ∑PAHs ranges from 26.3 to 1701.5 ng/g. To trace the sources of PAHs, the molecular ratio methods, such as LMW/HMW, Fla/(Fla + Pyr) and BaA/(BaA + Chr), were used respectively. In most cases, PAHs in Liuxi Ricer were pyrogenic. These sources included combustion of petroleum fuel, and burning of biomass fuels like coal and wood. The toxicity of fluorene and fluoranthene in Liuxi River was evaluated. The results showed that there was oxidative damage induced by H2 O2 at a fluorine concentration of 50 mg/L, and fluoranthene could induce oxidative stress and DNA damage. In addition, the damage stress induced by fluoranthene was stronger than by fluorine under the same concentrations.